(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the knowledge and practice of drowning prevention of students at Pham Hong Thai Secondary School, Thach Da commune, Me Linh district, Hanoi city, 2023. Subject and method: A Cross-sectional descriptive study conducted on 828 students from grades 6 to 9 studying at Pham Hong Thai secondary school from September 2023 to April 2024. Results: The percentage of students at Pham Hong Thai Secondary School, Me Linh district, Hanoi city with good knowledge about drowning prevention was 52.7%. The percentage of students with good practices in drowning prevention was 34.7%. 47.5% of students knew how to swim, of which 44.7% of students practiced good safety when swimming. When encountering dangerous situations underwater, 86.2% of students practiced drowning self-rescue skills well. The rate of 50.2% of students practiced well to ensure safety when traveling by water. The percentage of students practicing well in rescuing drowning victims and providing first aid to drowning victims were 57.5% and 44.3%, respectively. Conclusion: The current state of knowledge and practice of drowning prevention among middle school students is still low. Intervention programs on teaching swimming skills and self-rescue skills, rescuing drowning victims and first aid for drowning need to be implemented in school health programs.